A textbook of basic electronics - Raychaudhuri, Barun (Chhaya Prakashani, 2010)
A textbook of basic electronics / Raychaudhuri, Barun. -- Kolkata: Chhaya Prakashani, 2010 621.381 R263e2 No. of Copies : 2